Utilization of absolute monocyte counts to predict cardiovascular events in people living with HIV. Issue 4 (8th December 2020) - Bogorodskaya, M; Lyass, A; Mahoney, TF; Borowsky, LH; Sen, P; Swirski, FK; Srinivasa, S; Longenecker, CT; Massaro, JM; D'Agostino, RB; Triant, VA
Abstract : Objectives: Cardiovascular risk is increased in people living with HIV (PLWH). In HIV‐uninfected populations, total absolute monocyte count (AMC) has been shown to be predictive of future cardiovascular events (CVEs). We sought to determine whether AMC predicts CVEs in PLWH independent of established and HIV‐related cardiovascular risk factors. Methods: We identified all PLWH within the Partners HIV Cohort without factors that could confound the monocyte count. CVE was defined as fatal or non‐fatal acute myocardial infarction or ischaemic stroke. Baseline‐measured AMC was defined as the average of all outpatient AMC counts a year before and after the baseline date. Multivariable Cox proportional hazards models were used to assess the association of baseline AMC with CVEs. Results: Our cohort consisted of 1980 patients, with median follow‐up of 10.9 years and 182 CVEs. Mean (± SD) age was 41.9 ± 9.3 years; 73.0% were male. Mean CD4 count was 506.3 ± 307.1 cells/µL, 48% had HIV viral load (VL) < 400 copies/mL, and 87% were on antiretroviral therapy. Mean AMC was 0.38 × 10 3  ± 0.13 cells/µL. In multivariable modelling adjusted for traditional CV risk factors, CD4 cell count, and HIV VL, AMC quartile 2 (Q2) (HR = 1.01, P  = 0.98), Q3 (HR = 1.07, P  = 0.76), and Q4 (HR = 0.97, P  = 0.89) were not significantly predictive of CVE compared with Q1. Discussion: Baseline AMC was not associated with long‐term CVEs in PLWH. AMC obtained in routine clinical encounters does not appear to enhance CV risk stratification in PLWH.